(NiZ ISTORII RUSSKOJ MUZYKALXNOJ KRITIKI (BXIX (NWEKA s (NISTORIQs - (Ne(B. (NgORDEEWA(B.s ((NmOSKWAs (NmUZYKAs, 1950)
XIX (NWEK BYL rOSSII WREMENEM NEBYWALOGO MOGU^EGO KULXTURNOGO POD_EMA(B.s
Keywords: (NISTORIQs